Efeito do processo ECAP sobre a microestrutura e as propriedades mecânicas da liga Ti-35Nb-0,15Si e do Ti CP - Silva, Késia Filadélfia Dionizio (2017)
This work investigated the effect of different types of homogenization on the microstructure and the cold deformation behavior of Ti-35Nb-0,15Si alloy. Homogenization was performed under two conditions. Condition 1: treatment in ambient air at 1000 °C for 8, 24, 48, 72, 96 and 120 hours. Condition 2: treatment in argon atmosphere at 1000 °C for 8 hours. For the cold deformation study samples of the Ti-35Nb-0,15Si alloy and samples of Ti CP were deformed by ECAP with up to 8 passes, using the routes A and BC in a matrix with angle of intersection between the channels of Φ = 120º. The microstructural characterization was performed in the internal and external regions with the aid of optical microscopy, scanning electron microscopy and X-ray diffractograms. Vickers microhardness measurements were performed to evaluate the changes caused by deformation. In the ambient air atmosphere the samples showed the presence of the oxide layer influencing the hardness and the level of cold deformation. With the deformation of Ti-35Nb-0,15Si by ECAP it was possible to refine the structure and increase the hardness with increasing the number of passes. XRD analysis showed the presence of the α” phase induced by deformation. With the Ti CP deformed by ECAP, it was possible to analyze the microstructural evolution throughout the sample.